Chlorophyll 2017
DOI: 10.5772/67610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Phosphorus Concentrations on the Chlorophyll Responses of Salvia chamelaeagnea (Lamiaceae) Grown in Hydroponics

Abstract: Salvia chamelaeagnea (Lamiaceae) is a slow growing water-wise evergreen shrub originating from the western province of South Africa. It is an attractive landscape, and S. chamelaeagnea is a medicinal plant. It is important to develop enhanced cultivation protocols that could result in high yield and high-quality medicinal materials. Chlorophyll is a fundamental part of the light-dependent reactions of the photosynthesis process. This chapter investigates the effects of four phosphorus concentrations and three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…As a result, maintaining cellular phosphorus homeostasis is essential for ensuring the normal function of various physiological and biochemical processes ( Raghothama, 2015 ). The elevated P concentration observed in the 2C system compared to the 1C system may likely be attributed to an increase and fluctuations in pH within the 1C regime, a phenomenon in line with the findings of Lefever et al. (2017) .…”
Section: Discussionsupporting
confidence: 83%
“…As a result, maintaining cellular phosphorus homeostasis is essential for ensuring the normal function of various physiological and biochemical processes ( Raghothama, 2015 ). The elevated P concentration observed in the 2C system compared to the 1C system may likely be attributed to an increase and fluctuations in pH within the 1C regime, a phenomenon in line with the findings of Lefever et al. (2017) .…”
Section: Discussionsupporting
confidence: 83%
“…In the earlier studies in the literature, phosphorus (P) is required in relatively large amounts for the biosynthesis of primary and secondary metabolites (Marschner 2002), Seeds have the highest concentration of P in a mature plant, and P is required in large quantities in young cells, such as shoots and root tips, where metabolism is high and cell division is rapid (Khalid and Shedeed 2015). Phosphorus fertilization significantly induced a higher chlorophyll production of Salvia chamelaeagnea (Lefever et al, 2017). Pedone-Bonfim et al, (2018) reported that the plant growth is severely restricted at low P levels, but the addition of AMF appears to remove this limiting factor.…”
Section: Bio-pesticides and Biological Control 553mentioning
confidence: 99%
“…The production of chlorophyll in the plant could be influenced by an interaction of environmental factors with biochemical, physiological, and genetic characteristics of plant, such as the influence of environmental factors on chlorophyll production by Festuca arundinacea [20] and Salvia chamelaeagnea (Lamiaceae) [21]. Plant cell and tissue culture strategies are an attractive alternative to the use of whole plants for the production of pigments and have been the subject of extended research in the last decades.…”
Section: Resultsmentioning
confidence: 99%